TINGKAT KEBERHASILAN TRANSFER EMBRIO (TE) BERDASARKAN KEGIATAN SELEKSI RESIPIEN DAN PELAKSANAAN TE DARI TAHUN 2018 SAMPAI DENGAN 2021 DI KABUPATEN ROKAN HULU - Ade Hapari S.Pt (SUNGKAI, 2022)
Implementation of the application of embryo transfer technology (ET), requires a program that can meet the wishes of the livestock community in terms of improving the genetic quality of liverstock quickly. The program is related to the proposal of beef cattle by field officers, selection of recipient cattele by the embryo transfer team which includes: exterior assessment, such as the Body Condition Score (BSC), interior assessment such as rectal palpation of the internal genitals (cervix, uterus an ovaries). The next activity is the implementation of embryo transfer such as how handle recipient cattel; wheather the recipient has been in Artificial Insemination (AI) (twinning program) or single ET, epidural anastesi, thowing frozen embryos in water at 38℃, insertion of embryo straw into the ET gun/plastic ET, rectal palpation, cervical examination, insertion of the ET gun, embryo deposition to the uterine horn, recording the results of ET, examination of pregnancy results of ET at the age of 2 months, monitoring of recipients who are already pregnant until elivery, reporting the results of single ET briths and ET twinning(AI/ET). This technical report is the result of the embryo transfer (ET) program activities that took place from 2012,2018,2019,2020,and 2021, which in this technical report discusses the success rate of embryo transfer (ET) based on recipient selection and impelemtation activities embryo transfer (ET).